Nano Online 2017
DOI: 10.1515/nano.0034.2015-0069
|View full text |Cite
|
Sign up to set email alerts
|

Strategic role of nanotechnology for production of bioethanol and biodiesel

Abstract: In spite of the limited sources of fossil fuels, energy demand has been considerably increased since the last century. The problems associated with global warming due to rising atmospheric greenhouse gas levels and scarcity of fossil fuels make it imperative to reduce our heavy dependency on fossil fuels. These reasons forced countries throughout the world to search for new fuel alternatives. Biofuel have gathered considerable attention due to their inherent benefits, like lower greenhouse gas emission, renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Because of the recalcitrant property, it is difficult to efficiently extract the cellulose, in order to apply it. Hence, the lignocellulose biomass has also been refined into bioethanol and biodiesel by chemical or biological catalysis process [15][16][17], or been prepared into biomass based carbon materials for supercapacitor electrode [18,19]. A specific cellulose such as nanocrystal [20][21][22] or nanofibers cellulose hydrogels [23][24][25] has been applied for 3D printing to fabricate 3D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the recalcitrant property, it is difficult to efficiently extract the cellulose, in order to apply it. Hence, the lignocellulose biomass has also been refined into bioethanol and biodiesel by chemical or biological catalysis process [15][16][17], or been prepared into biomass based carbon materials for supercapacitor electrode [18,19]. A specific cellulose such as nanocrystal [20][21][22] or nanofibers cellulose hydrogels [23][24][25] has been applied for 3D printing to fabricate 3D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have recently demonstrated that nanotechnology can also offer easy, green, efficient, and economically viable approaches for the pretreatment of LB . Bootsma and Shanks demonstrated the catalytic activity of mesoporous silica functionalized with sulfonic and carboxylic acid in the hydrolysis of cellobiose used as a model compound.…”
Section: Nanotechnology For the Pretreatment Of Lbmentioning
confidence: 99%
“…Most of these were reported to be promising methods but they have certain limitations, which restrict their routine use to some extent. Hence, considering the need for research to develop new alternatives to existing pretreatment methods, nanotechnology could offer promising solutions because it has the potential to change the characteristics of feed materials and biocatalysts used for biofuel production . However, some recent studies have shown that nanotechnology in general and acid‐functionalized magnetic nanoparticles in particular can be used effectively for the pretreatment of some LB .…”
Section: Introductionmentioning
confidence: 99%
“…Different nanomaterials like carbon nanotubes, magnetic, and metal oxide nanoparticles are advantageous for sustainable bioenergy production. In the biofuels and bioenergy field, nanotechnology has different applications, such as modification of feedstock, development of more efficient catalyst, and replacement of enzyme by nanostructures 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…In the biofuels and bioenergy field, nanotechnology has different applications, such as modification of feedstock, development of more efficient catalyst, and replacement of enzyme by nanostructures. 19,20 Iron oxide nanoparticles have a wide variety of scientific and industrial applications, such as catalysis, drug delivery, and biomedical applications. The advantage of the iron-based catalytic conversion is recycling and separation.…”
Section: Introductionmentioning
confidence: 99%